Biglycan and reduced glycolysis are associated with breast cancer cell dormancy in the brain - Sunderland, Ashley; Williams, Jennifer; Andreou, Tereza; Rippaus, Nora; Fife, Christopher; James, Fiona; Kartika, Yolanda Dyah; Speirs, Valerie; Carr, Ian; Droop, Alastair; Lorger, Mihaela (Frontiers in Oncology, 2023)
Exit of quiescent disseminated cancer cells from dormancy is thought to be responsible for metastatic relapse and a better understanding of dormancy could pave the way for novel therapeutic approaches. We used an in vivo model of triple negative breast cancer brain metastasis to identify differences in transcriptional profiles between dormant and proliferating cancer cells in the brain. BGN gene, encoding a small proteoglycan biglycan, was strongly upregulated in dormant cancer cells in vivo. BGN expression was significantly downregulated in patient brain metastases as compared to the matched primary breast tumors and BGN overexpression in cancer cells inhibited their growth in vitro and in vivo. Dormant cancer cells were further characterized by a reduced expression of glycolysis genes in vivo, and inhibition of glycolysis in vitro resulted in a reversible growth arrest reminiscent of dormancy. Our study identified mechanisms that could be targeted to induce/maintain cancer dormancy and thereby prevent metastatic relapse.